UNDERWATER CANYONS OF THE SOUTHWESTERN OUTSKIRTS OF SOUTHERN BAIKAL AS PRESUMABLE TRANSITERS OF TECHNOGENIC MATERIALS TO THE ABYSSAL SURFACE - E. E. Kononov; N. A. Gubin (Геодинамика и тектонофизика)
Numerous publications by domestic and foreign authors deal with a significant role of underwater canyons in transit of loose material from the littoral to the abyssal surfaces of the seas. Lake Baikal fully corresponds in its hydrodynamic and bathymetric parameters to sea water basins, and the Baikal canyons are similar in their morphological and morphometric factors to sea canyons. A digital elevation model of the southwest underwater tip of the lake, generated based on a large array of bathymetric data, allowed identifying clearly defined valleys of the Shamanka and Slyudyanka canyons. The data obtained during the study of the canyon-valley area, carried out using special geophysical measuring instruments – Kongsberg EM710S multibeam echosounder and Knudsen CHIRP 3260 profilograph, – and analysis of the published materials showed a rather high degree of confindness of coarse debris to the canyon valleys and alluvial fans which implies their significant role in sediment transit. It has been shown that high seismicity of the Baikal basin and active wave conditions give rise to the formation of movable loose sediment masses and to the occurrence of gravity flows in the canyon valleys. Climate changes over the last decades contribute also to permafrost decomposition in the Baikal basin and to new-sediment transport into the lake. It is implied that an intensive development of the coastline leads to the coastal accumulation of a large amount of industrial and municipal contaminants which can move through the canyons to different distances into the lake water area. To date, there is no definite answer to the question about an actual role of underwater canyons in the transit of technogenic wastes to the abyssal lake surface. This requires organized large-scale specialized fieldwork with the use of high-precision geological-geophysical measuring instruments, and systematic sampling and thorough analysis of the bottom material.